2020
DOI: 10.1002/btpr.3067
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of ferulic acid into aroma compounds by newly isolated yeast strains of the Latin American biodiversity

Abstract: Nine yeast strains isolated from Latin American biodiversity were screened for ferulic acid (FA) consumption and conversion into aroma compounds such as vanillin, vanillic acid (VA), and 4-vinylguaiacol (VG). Selected strains (Rhodotorula mucilaginosa UFMG-CM-Y3647, UFMG-CM-Y2190, UFMG-CM-Y665) were evaluated in flask experiments to investigate the influence of the pH media on bioconversion and a two-step process was conducted to maximize the metabolites production. The effect of pH was found to be significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 70 publications
(181 reference statements)
0
11
0
Order By: Relevance
“…A number of yeasts, some of them isolated from soil, have been described to utilize a range of lignin-derived aromatic monomers, such as FA, HBA, CA, PCA, and VA, as sole carbon and energy sources [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The biodegradation of mixtures of lignin-derived model compounds, as described in our study, has only been reported for bacteria [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of yeasts, some of them isolated from soil, have been described to utilize a range of lignin-derived aromatic monomers, such as FA, HBA, CA, PCA, and VA, as sole carbon and energy sources [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The biodegradation of mixtures of lignin-derived model compounds, as described in our study, has only been reported for bacteria [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…An important factor in biotechnological applications is temperature. The degradation of lignin-derived aromatic monomers by yeasts has been generally assessed under mesophilic temperature conditions (mostly at 24–30 °C; [ 3 , 9 , 16 , 18 , 19 , 21 , 22 ]). Sampaio [ 17 ] applied temperatures in the range of 17–22 °C.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial fermentation has been gaining avor scientists and manufacturers attention for decades because of avor compounds produced enzymatic and microbiological processes are de ned as "natural avors" (European Council Directive, Directive 88/388/88 EEC). The growing of perception and desire for natural products by consumer also drawn on the development biotechnological process for the natural bio-products [4]. Today, agricultural wastes or by-products are emphasized as favorable sources in terms of economic and environmental impact to obtain a high added value product by microbial fermentation.…”
Section: Introductionmentioning
confidence: 99%